Influence of Incorporating MWCNTs on Some Physical Characteristics of Blend Nanocomposites - Jassim , Lubna Abdul-Aziz; Jawad , Mohammed Kadhim (Iraqi Journal of Physics, 2024)
Nanocomposite membranes made of chitosan (Cs) concentrations, and polyvinyl alcohol (PVA) with a fixed ratio of (60:40), then incorporated with different concentrations of multi-walled carbon nanotubes (MWCNTs) (1, 1.5, 2, 2.5, and 3%) were created using the solution cast method. The membranes were identified using UV-vis spectroscopy, Fourier transform infrared (FTIR), and X-ray diffraction (XRD). The results demonstrated that the samples were sufficiently stable, and the interactions between nanoparticles and polymers were generally negligible. XRD patterns showed a crystalline phase of PVA, an amorphous phase of chitosan, and a more crystalline phase as MWCNTs were introduced. In particular, at high percentages of MWCNTs, the dominant phase (002), connected to MWCNTs, was shifted to a higher value. The UV-vis spectroscopy of the sample showed only one absorption peak at about 230 nm and no other peaks. This may be due to transparency in PVA and Cs. The band gap energy decreased when higher percentages of MWCNTs were added to the mixture.